Niobium carbide–mediated photothermal therapy for infected wound treatment - Ren, Junyu; Da, Junlong; Wu, Wei; Zheng, Ce; Hu, Narisu (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial infections on the surface skin wounds can significantly reduce the rate of wound healing, which also can lead to serious systemic infections. Antibiotics are the first-line drugs for anti-infection treatment. However, the misuse and overuse of antibiotics have led to the emergence of bacterial resistance. Therefore, a new antimicrobial strategy is needed urgently. Photothermal therapy (PTT), a novel efficient therapeutic technique, can produce irreversible cell damage to induce the death of bacteria, which has exhibited great potential in infected-wound healing. Here, we reported a new photothermal agent (PTA) niobium carbide (NbC) nanoparticles with outstanding near-infrared (NIR) absorption property. Meanwhile, NbC nanoparticles could convert NIR laser irradiation energy into localized heat for photothermal treatment. The vitro antimicrobial experiments revealed that the NbC nanoparticles performed excellent antimicrobial effects against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) bacteria. Moreover, NbC nanoparticles accelerated the E. coli-infected wounds healing process, reduced inflammatory response, and exhibited good bio-safe ability in vivo. Altogether, NbC nanoparticles is an efficient photothermal agent for antimicrobial treatment and a bio-safe material with low toxicity in vivo.